2016
DOI: 10.21767/2171-6625.100094
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Exposure to Lead during Pregnancy Affects Spatial Learning, Memory and Neurogenesis in Hippocampus of Young Rats

Abstract: Lead is toxic to all organ systems. Central nervous system has received much attention because of the impact of lead exposure on cognitive and behavioral development in children. We investigated the effects of in utero lowdose exposure to lead on neurogenesis in hippocampus and spatial learning and memory in young rats. Wistar rats, after establishing pregnancy, were given drinking water with 0.1% lead acetate until parturition. Control animals received deionized water. The hippocampus of lead-exposed rats sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In this way, although prevalence of lead is considered as an ecological threat for all regardless of age (31) but pregnant women and young children are at the highest risk. A wide range of research showed that the level of lead in newborns exceeded 10 microgram / deciliter in blood and exceeded a standard limit (32).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, although prevalence of lead is considered as an ecological threat for all regardless of age (31) but pregnant women and young children are at the highest risk. A wide range of research showed that the level of lead in newborns exceeded 10 microgram / deciliter in blood and exceeded a standard limit (32).…”
Section: Introductionmentioning
confidence: 99%